Konsep Viktimisasi dalam Perspektif Viktimologi - Zikra Askalani Azis; Nurliman Prasetyo (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Victimology is a branch of criminal law that focuses on the study of victims of crime, including the process of victimization and the factors that contribute to it. In the criminal justice system, attention has often been centered on offenders, while the position of victims tends to be neglected. This study aims to analyze the concept of victimization from the perspective of victimology and to understand how individuals can become victims within the context of criminal acts. The research method used is normative legal research with a conceptual approach, relying on secondary data such as legal literature and scholarly works. The results indicate that victimization is influenced by various factors, including social, economic, and psychological conditions, as well as the interaction between victims and perpetrators. Victimology plays an important role in providing a more balanced perspective in the criminal justice system by emphasizing the protection and rights of victims. Therefore, a deeper understanding of victimization is essential in formulating fair and victim-oriented legal policies.